α-synuclein inhibitor from endophytic fungi - Vats, Sheetal (My University, 2004)
The present study was oriented towards the exploration of α-synuclein disaggregation potential of fungal endophytes isolated from Camellia sinensis and Malus domestica from Assam and Himachal Pradesh inhabiting biodiversity hotspots of India. Out of 79 endophytic fungal isolates, culture filtrates of 4 isolates were found to exhibit disaggregation potential due to anti-oxidant effect analysed via preliminary screening NBT assay. The cell free culture filtrate of “59CSLEAS” was further screened by using various in vitro assays viz. ThT, Sandwich ELISA and DCFH-DA and found as the most potent. The crude chloroform residue of endophytic fungal isolate 59CSLEAS was found to disaggregate oligomeric protein up to 56.5 % via Sandwich ELISA technique. The potential endophytic fungus was identified using morphological and molecular tools as Fusarium oxysporum. Another approach i.e., in silico analysis suggested role of antioxidants compounds present in Camellia sinensis in inhibition of protein oligomerization. Further, the crude chloroform residue of Fusarium oxysporum was fractionated into 11 major fractions using TLC and column chromatography. The fraction 10 was found to exhibit maximum α-synuclein disaggregation potential with DC50 of 1.101 ± 0.04 µM. Fraction 10 appeared white, light sensitive, and analysed as potent antioxidant having high free radical scavenging roperties IC50 0.12 ± 0.04 mg/ ml ascertained via DPPH assay. Mass spectra of bioactive fraction showed parent ion peak at 459.1208 m/z. Further, IR spectra confirmed the presence of hydroxyl and aromatic carbonyl groups. 1H-NMR and 13C-NMR spectra of bioactive fraction 10 tentatively identified the compound to be gallate ester. The ESI MS, FTIR, and NMR spectra of data of bioactive fraction 10 was found to be identical to Epigallocatechin gallate. This is the first report of a plant catechin being produced by an endophytic fungus which is also a potent alpha-synuclein disaggregator. The present study establishes that endophytic fungi are prolific sources of novel inhibitors/ disaggregators against neurodegenerative disorders and oxidative stress. The isolation of Epigallocatechin gallate, as alpha-synuclein disaggregator from endophytic fungi further warrants its further evaluation by in silico simulation studies and optimizing QSAR (Quantitative Structure Activity Relationship) for its development into a pharmacophore in management of oxidative stress related disorders since Epigallocatechin gallate is already being used as a nutraceutical.
Keywords: alpha-synucelin; endophytic fungi; Parkinsons disease; Camellia sinensis